Effect of infill pattern on the mechanical properties of polydopamine‐coated polylactic acid orthopedic bone plates developed by fused filament fabrication. Issue 2 (28th November 2022) - Sharma, Shrutika; Gupta, Vishal; Mudgal, Deepa
Abstract: Distal fractures are the most commonly experienced type of fractures that require fixation of bone plates for healing of fractured bones. Poly Lactic Acid (PLA)‐based bone plates are porous and light in weight. However, they lack mechanical properties that limit their application in biomedical field. Polydopamine coating has been witnessed to undergo covalent interactions, enhancing the mechanical properties of the substrate. The present study is based on the fabrication of PLA‐based bone plates using Fused Filament Fabrication with varying infill patterns. The infill patterns in the study include octet, cubic, grid, concentric, lines, and gyroid. Thereafter, polydopamine coating was deposited on these bone plates using direct immersion coating method. In the study, the effect of infill pattern on coating deposition and modification of mechanical properties has been studied. The microscopic images of fractured bone plates were captured. It was concluded that polydopamine coating was successful in improving mechanical properties for all infill patterns. The findings suggested that a concentric pattern should be used for applications that require both high mechanical strength and maximum elongation at break because elongation at break is higher for concentric patterns than gyroid patterns. Also, for applications requiring only high mechanical strength, a gyroid pattern should be used. Abstract : PLA based distal ulna small locking bone plates have been fabricated using FFF with varying infill patterns. The infill patterns in the study include octet, cubic, grid, concentric, lines and gyroid. The polydopamine coating was deposited on bone plates using direct immersion method. In the study, the effect of infill pattern on coating deposition and mechanical properties have been studied.